2019
DOI: 10.1007/s00264-019-04426-7
|View full text |Cite|
|
Sign up to set email alerts
|

Twenty common errors in the diagnosis and treatment of periprosthetic joint infection

Abstract: Background Misconceptions and errors in the management of periprosthetic joint infection (PJI) can compromise the treatment success. The goal of this paper is to systematically describe twenty common mistakes in the diagnosis and management of PJI, to help surgeons avoid these pitfalls. Materials and methods Common diagnostic and treatment errors are described, analyzed and interpreted. Results Diagnostic errors include the use of serum inflammatory biomarkers (such as C-reactive protein) to rule out PJI, inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 81 publications
(105 reference statements)
2
51
0
15
Order By: Relevance
“…Systemic inflammation markers and synovial fluid biomarkers have been a hot research topic in recent years [2,3]. Compared with blood tests, synovial fluid tests are more dependent on doctors' personal operational experience; some test results were decided by the tester's subjective judgement, and the procedures of joint aspiration can easily affect the final result [4][5][6][7]. Therefore, blood tests may be easier to use, more stable, more cost-effective and easier to popularize for diagnosing PJI.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation markers and synovial fluid biomarkers have been a hot research topic in recent years [2,3]. Compared with blood tests, synovial fluid tests are more dependent on doctors' personal operational experience; some test results were decided by the tester's subjective judgement, and the procedures of joint aspiration can easily affect the final result [4][5][6][7]. Therefore, blood tests may be easier to use, more stable, more cost-effective and easier to popularize for diagnosing PJI.…”
Section: Introductionmentioning
confidence: 99%
“…First, 2 of the included studies only had 11 infection cases [4,20], and the small sample size potentially influenced the overall results. Second, although the diagnostic standard was always used for identifying infection cases, the use of different diagnostic standards to estimate the value of diagnostic tools resulted in different sensitivity and specificity values [31]. Third, in the antibiotic subgroup, we found that the combination of serum testing without antibiotic therapy further improved diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 84%
“…First, two of the included studies only had 11 cases of infection [4,23], and the small sample size potentially affected overall results. Second, although the diagnostic standard was always used to identify cases of infection, the use of different diagnostic standards to estimate the value of diagnostic tools resulted in different sensitivity and specificity values [34]. Third, based on the current publication, two studies showed that the combined method may improve diagnostic results compared to single use in low virulence infections [9,23].…”
Section: Discussionmentioning
confidence: 95%